Metaphoric Expression of Al-Meraj in Urdu Ghazal - Tahira Inaam; Dr. Zamurrad Kousar (Zaban-o-Adab, 2021)
On the face of it, Ghazal seems to be bound by restraints but it is an unparalleled genre when it comes to the variety of dimensions. Ghazal has the power to conceal reality within layers of metaphoric expression. All aspects of physical and spiritual reference to humankind are intertwined in its essence. In our instance, the symbolism and intricacies of the Ghazal have benefited equally from the region, civilisation, beliefs, social interaction and history.Mythical and historic as well as religious references have been expanding the perimeter of meaning in terms of allusions and metaphor. In our instance, Urdu Ghazal's use of historic allusions and symbolism with regard to religious reference has been analysed. However, similar endeavours have not taken place in order to trace the significance of Al-Miraaj in the intricate layers of Ghazal. Generally, the Prophetic miracles (SAW) have been associated with the literature of Naat. Yet, analysing the ambiguity and mystery of Ghazal in view of the above-mentioned aspect will certainly be a matter of great interest. In all ages, Ghazal has demonstrated various manners of expression related to Al-Miraaj.”